I wonder why : snakes shed their skin - "O,Neil, Amanda" (Kingfisher London, 2011)
"I Wonder Why Snakes Shed Their Skin" by Amanda O'Neill. This engaging children's book serves as an introduction to reptiles, addressing questions such as "Which lizard has a frightful frill?" and "Which turtle kicks up a stink?" It features topics like snorkeling turtles, crocodiles, and camouflaged snakes, aiming to both amuse and educate young readers.